Understanding mental health help-seeking preferences of Chinese young overseas students, and their perceived barriers and facilitators to seek help - Liu, Fengjiao (Journal of Education Culture and Society, 2021)
Aim. The research explores the mental health help-seeking preferences of Chinese young overseas students (CYOS) as well as their perceived barriers and facilitators to seek help. Methods. Eight Chinese young overseas students who are currently studying in the US were interviewed, and a thematic analysis was undertaken on their responses. Conclusions. Five barriers and six facilitators were identified. Young overseas students considered perceiving the problems as not serious, negative attitude toward help seeking, being not willing to burden somebody else, lack of understanding of the process of mental health support, and issues of confidentiality and trust as the most important barriers to help seeking. Facilitators include positive attitudes towards help seeking, positive relationship with help providers, perceiving the problem as serious, easy access, confidentiality and trust, and previous habit of seeking help. Research restrictions. The samples are relatively homogeneous and could not represent all CYOS and thus lacked generalizability. Only interviews were applied for data collection, which has an impact on the credibility and trustworthiness of the research. Practical application. Strategies for improving help-seeking should focus on improving mental health literacy of these young people, their peers and parents, building positive relationships with help providers, and cultivating good help-seeking habits before they go abroad.